Peningkatan Kompetensi Guru dalam Pengolahan Data Menggunakan Microsoft Excel melalui Pelatihan di Kecamatan Jatibarang Kabupaten Indramayu - Suyono, Suyono; Siregar, Dania; Zahra, Khoiruz; Abdurrahim, Muhamad Afif (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2025)
Data processing skills based on information and communication technology (ICT) are essential competencies for teachers, both in educational administration and in supporting data-driven learning processes. However, field conditions indicate that a number of teachers in Indramayu Regency still have limited capacity to process and analyze data digitally. This community service program aimed to enhance teachers’ competencies in data processing and analysis using Microsoft Excel through a structured training program. The training was conducted at SMK Assalaam, Jatibarang District, Indramayu Regency, and was attended by teachers from various subject areas. The implementation methods included socialization, initial assessment, practice-based training using a learning-by-doing approach, and evaluation of both the process and outcomes through pre- and post-training questionnaires. The training materials focused on descriptive statistical data processing and data visualization, including the creation of bar charts, pie charts, histograms, and line charts, as well as the calculation of measures of central tendency and dispersion such as mean, median, mode, variance, and standard deviation using Microsoft Excel. The evaluation results indicate an improvement in participants’ ability to process data digitally, as reflected in their capacity to utilize Excel formulas and the Data Analysis feature for simple data analyses relevant to teachers’ professional tasks. In addition to improved technical competence, this program also produced outcomes in the form of enhanced data literacy and increased readiness of teachers to apply ICT-based data processing to support decision-making and instructional administration. This activity is expected to serve as a training model that can be replicated in other schools within Indramayu Regency. Abstrak Keterampilan mengolah data berbasis teknologi informasi dan komunikasi (TIK) merupakan kompetensi penting bagi guru, baik dalam administrasi pendidikan maupun dalam mendukung proses pembelajaran berbasis data. Namun, fakta di lapangan menunjukkan bahwa sebagian guru di Kabupaten Indramayu masih memiliki keterbatasan dalam mengolah dan menganalisis data secara digital. Kegiatan pengabdian kepada masyarakat ini bertujuan untuk meningkatkan kompetensi guru dalam mengolah dan menganalisis data menggunakan Microsoft Excel melalui program pelatihan terstruktur. Pelatihan dilaksanakan di SMK Assalaam Kecamatan Jatibarang Kabupaten Indramayu dan diikuti oleh guru dari berbagai bidang studi. Metode pelaksanaan meliputi sosialisasi, asesmen awal, pelatihan berbasis praktik (learning by doing), serta evaluasi proses dan hasil pelatihan menggunakan kuesioner pre dan post. Materi pelatihan difokuskan pada pengolahan data statistik deskriptif dan visualisasi data, meliputi pembuatan diagram batang, diagram lingkaran, histogram, dan diagram garis, serta perhitungan ukuran pemusatan dan penyebaran data seperti mean, median, modus, variansi, dan simpangan baku dengan Microsoft Excel. Hasil evaluasi menunjukkan adanya peningkatan kemampuan peserta dalam mengolah data secara digital, ditandai dengan kemampuan peserta dalam memanfaatkan fitur Data Analysis dan formula Excel untuk analisis data sederhana yang relevan dengan tugas profesional guru. Selain peningkatan kompetensi teknis, kegiatan ini juga menghasilkan luaran berupa meningkatnya literasi data dan kesiapan guru dalam menerapkan pengolahan data berbasis TIK untuk mendukung pengambilan keputusan dan administrasi pembelajaran. Kegiatan ini diharapkan menjadi model pelatihan yang dapat direplikasi pada sekolah lain di wilayah Kabupaten Indramayu.